Using Lee Model Codes to derive the Scaling Laws and performance of Dense Plasma Focus machines working in deuterium gas - Arwinder, Singh*; Lee, Sing; Saw, Sor Heoh (2019)
n this paper, a total of 26 Mather type anode, Dense Plasma Focus (DPF) machines, working in deuterium gas, were analysed using numerical experimentation. It was found that the numerically computed neutron yields were within a factor of 3 when compared with the measured yields. The scaling laws that relate the numerically computed neutron yield (Yn) to stored energy in the plasma (E_0), peak current of the plasma (I_peak) and its pinch current (I_pinch) were found to be Yn ~ , Yn ~ , Yn ~ .When the values of the measured yield were combined with the numerically computed yields, the relation of Yn ~ was obtained, which was closed to the generally accepted scaling law of Yn ~ . It was also found that for high inductance machines, the numerical code gave less yield (typically 10 times) than what was obtained experimentally. The difference may be due to the extended dips (ED) attributed to anomalous resistivity which are observed in the measured current traces of the high inductance machines. These extended dips are not modeled in the code.